Effect of electrolyte concentration on the electrochemical properties of an AB5-type alloy for Ni/MH batteries - Ruiz, Fabricio Carlos (2013)
This publication is the first of a series of three that we have undertaken to study the effect of electrolyte concentration on electrode performance. Here, the electrochemical properties of an AB5-type alloy, namely LaNi3.6Co0.7Mn0.4Al0.3, are investigated using different KOH electrolyte concentrations (i.e. 2 M, 4 M, 6 M and 8 M). The next two publications will be concerned with an AB2-type alloy and a Mg-based alloy, respectively. From the present study, the 6 M and 8 M electrodes were those that exhibited faster activation, maximum discharge capacity values (∼325 mAh/g) and best performance under high-rate dischargeability. Nevertheless, the capacity loss rate increased as KOH concentration augmented. The electrochemical behavior is analyzed in terms of a physicochemical model based on the theory of porous electrodes. The fitting of electrochemical impedance spectroscopy data in terms of the model allowed determining kinetic parameters of the hydriding reaction, transport of hydrogen in the alloys and structural electrode parameters.